TECHNOLOGICAL INNOVATION DeNOX: A CONTRIBUTION FOR MITIGATION OF GREENHOUSE GAS - ALONSO, Vera Lucia Chaves; JUNIOR, Nelson ALONSO; JUNIOR, Sergio Silva BRAGA (Revista Brasileira de Engenharia de Biossistemas, 2012)
The adoption of sustainable technological innovation is an important strategy to organizational competitiveness that every company should consider value, considering that the present needs should not compromise the ability to meet future generations so that they can evolve. (Brundtland Commission, 1987). Allied to this, also added to ethics and transparency to the management of business organizations in the context in which they operate. Accordingly, the chemical industry with net sales in 2010 of $ 130.2 billion, also has a strong representation in the environmental impact. However, this same industry has invested in research and development of cleaner technologies to mitigate GEES. Associated with the reduction of NOx, a gas formed during the production process at high temperatures, this study aims to present some aspects of DeNOx technology used in the production process as well as provide possible both environmental and economic benefits. With the adoption of this new technology, a case study was carried out in a chemical industry located in Guaratingueta, the state of Sao Paulo/Brazil.